SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN HOMESTAY DI LOMBOK TIMUR BERBASIS ANDROID - Muhammad Wasil; Lalu Muhammad Samsu; Yupi Kuspandi Putra (Infotek: Jurnal Informatika dan Teknologi, 2020)
The geographical information system for mapping homestays in East Lombok is made as a medium for disseminating information in delivering homestay information for tourists who will visit Lombok, especially in East Lombok. This android-based information system presents images, descriptions and also locations displayed via google maps as directions to homestay locations based on choices from each homestay category. The information system can be used as well as supporting the tourism sector in Lombok and makes it easier for tourists to get complete and effective information. Geographic information system for mapping homestays in East Lombok based on Android is made with the Android Studio program and Google Maps as a guide for tourist locations. It can be concluded that this system is ready to be developed.DOI : 10.29408/jit.v3i1.1834